Constraints of molecular and stable isotopic compositions on the origin of natural gas from Middle Triassic reservoirs in the Chuanxi large gas field, Sichuan Basin, SW China. (December 2020) - Wu, Xiaoqi; Liu, Quanyou; Chen, Yingbin; Zhai, Changbo; Ni, Chunhua; Yang, Jun
Graphical abstract: Highlights: The Middle Triassic natural gas in the Chuanxi gas field is of oil-cracking gas. The gas experienced weak TSR alteration without the involvement of ethane. The gas pools were mainly formed by direct filling of secondary cracking gas. The gas was originated from source rocks of Late Permian mudstones and marlstones. Abstract: The Middle Triassic Leikoupo Formation in the Sichuan Basin is a gypsum-bearing stratum. The Chuanxi (CX) large gas field has been recently discovered in Middle Triassic reservoirs, with a controversial gas source. The gas geochemistry is analyzed in this study to investigate the gas origin and source. The H2 S-bearing dry gas in the CX gas field has an H2 S content ranging from 1.07% to 4.09%, with a gas souring index (GSI) of 0.0120–0.0438. The δ 13 C1, δ 13 C2, and δ 2 HCH4 values range from –31.8 to –30.4‰, from –32.9 to –29.6‰, and from –153 to –136‰, respectively. Genetic identification based on the geochemical characteristics suggests that the gas is an oil-type and derives from the secondary cracking of oil. According to the GSI and alkane carbon isotopes, the gas experienced weak TSR alteration without ethane. Potential high-quality source rocks include the Upper Permian mudstones and marlstones, as well as the Lower Cambrian mudstones, with a total organic carbon content generally higher than 2.0%. A comparison of the carbon isotopic compositions between ethane in the gas and kerogen and the hydrogen isotopic compositions of methane implies that natural gas has an affinity with the Upper Permian rather than the Lower Cambrian source rocks. The extremely low development of solid bitumen in the reservoirs suggests the inexistence of large-scale paleo-oil pools in the Leikoupo Formation. The Middle Triassic natural gas in the CX gas field originates from the Upper Permian Longtan Formation, where the gas pools are dominated by direct filling of secondary cracking gas.